Quality improvement initiative to improve the duration of kangaroo mother care for twin preterm neonates born at a tertiary care hospital in resource‐limited settings. (26th February 2021) - Arora, Pihu; Kommalur, Anitha; Devadas, Sahana; Kariyappa, Mallesh; Rao, Suman P N
Abstract : Aim: Kangaroo mother care (KMC) can be challenging in multiple births and more so in resource‐limited settings. This study aims at increasing the mean duration of KMC with early initiation in twin preterm neonates born at a tertiary care hospital using a quality improvement (QI) initiative. Methods: Barriers for poor KMC practice in twin preterm neonates born at the tertiary care hospital were analysed and baseline data were collected over a period of 4 months using a predesigned proforma. A QI team was formed and suggested solutions were prioritised through focus group discussions in the form of Plan‐Do‐Study‐Act (P‐D‐S‐A) cycles. Each cycle was of one‐month duration and three cycles were implemented, followed by the sustenance phase studied at 1‐month post‐implementation. Results: There were a total of 238 twin deliveries in the study period, of which 169 twin pairs were included in the study. At the end of implementation, the average day of initiation of KMC improved from 8th to 3rd day of life and the duration of KMC increased significantly from an average of 2.70 h/infant/day to 7.88 h/infant/day. Conclusion: This QI project focused on the improvement of KMC practice in twin preterm neonates in a tertiary care hospital where results were achieved with maximal utilisation of available hospital resources and low‐cost interventions. This study design is generalizable to other hospitals in resource‐limited settings where family participatory care can be strengthened to overcome the challenges of KMC in multiple births.